COMPUTERISATION OF RURAL SCHOOLS IN ZIMBABWE:CHALLENGES AND OPPORTUNITIES FOR SUSTAINABLE DEVELOPMENT (THE CASE OF CHIPINGE DISTRICT) - Shoorai Konyana; Elias Konyana (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2013)
In this paper we seek to explain the relevance of introducing Computer Studies in Zimbabwean rural schools as a means to reduce the access to Information Communication Technology (ICT) gap between rural and urban schools. We first acknowledge the efforts of various stakeholders in education in introducing the Information Communication Technology curriculum in rural schools in the last ten or so years as a commitment to bringing Science and Technology to the rural pupil. In addition, we further explore the progress that has been made by rural schools that received computers from the Head of State and Government over the years. In the process, however, we observe that most rural schools have not fully embraced the ICT curriculum owing to a number of challenges. Thus, we contend in this paper that most rural schools that received donated computers in Zimbabwe had not been capacitated to fully utilise the new technology for the benefit of pupils, teachers and the community. As a result, most of the gadgets have been lying idle in classrooms due to lack of either proper infrastructural facilities such as computer laboratories and electricity as well as lack of trained ICT teachers. In the final submission, we implore stakeholders in education to facilitate ICT development in rural schools in Zimbabwe so as to increase access, quality and equity in education for sustainable rural development in Southern Africa.